IPTEKS PENGENDALIAN SISTEM INFORMASI AKUNTANSI PENJUALAN PADA PT. HASJRAT ABADI CABANG MANADO - Tuhuteru, Gloria; Tirayoh, Victorina Z (Universitas Sam Ratulangi, 2018)
PT Hasjrat Abadi is an exclusive distributor for Toyota and Yamaha. This automotive company are preferred in eastern Indonesia. With modern sales, service facilities, and access to high-tech workshops, they achieving an average sales growth of 25% over the past few years. It proves the results of implementing maximum strategy. For Hasjrat Abadi, selling is one of important thing for this business. Sales are one of the important aspects in the continuity of the company's business processes and are routine activities that occur within the company. The sales process is a routine activity that produces information, and must have good mechanism. The sales cycle can occur in cash and credit. Cash payments can received directly by the company, but credit payment can occur in a longer time with billing procedures. The theoretical basis used in this article is sales accounting information system. Company need effective control to manage company sales, and has a system created to facilitate the company in conducting sales activities, namely the sales accounting information system. This article aims to find out how the control of the sales accounting information systems at PT Hasjrat Abadi in Manado, Indonesia. Keywords : accounting information system control, sales